2017
DOI: 10.1186/s12955-017-0623-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a smartphone-based coronary heart disease prevention (SBCHDP) programme on awareness and knowledge of CHD, stress, and cardiac-related lifestyle behaviours among the working population in Singapore: a pilot randomised controlled trial

Abstract: BackgroundCoronary heart disease (CHD) is the most prevalent type of cardiac disease among adults worldwide, including those in Singapore. Most of its risk factors, such as smoking, physical inactivity and high blood pressure, are preventable. mHealth has improved in the last decade, showing promising results in chronic disease prevention and health promotion worldwide. Our aim was to develop and examine the effect of a 4-week Smartphone-Based Coronary Heart Disease Prevention (SBCHDP) programme in improving a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 37 publications
4
71
0
6
Order By: Relevance
“…The majority of studies ( n = 11) recruited employees who were identified as desk-based or office workers, 32 , 37 39 , 41 43 , 45 , 46 , 48 , 49 three studies included nurse or health professionals 26 , 31 , 35 and the remaining eight studies recruited employees from a government department, 33 large unnamed organizations, 27 , 36 manufacturing plant employees 34 , 44 or a mix of businesses and organizations combined together. 28 , 40 , 47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies ( n = 11) recruited employees who were identified as desk-based or office workers, 32 , 37 39 , 41 43 , 45 , 46 , 48 , 49 three studies included nurse or health professionals 26 , 31 , 35 and the remaining eight studies recruited employees from a government department, 33 large unnamed organizations, 27 , 36 manufacturing plant employees 34 , 44 or a mix of businesses and organizations combined together. 28 , 40 , 47 …”
Section: Resultsmentioning
confidence: 99%
“… 27 , 36 , 40 The last six studies were conducted in Sweden, 41 , 43 Japan, 42 , 44 Norway 28 and Singapore. 47 …”
Section: Resultsmentioning
confidence: 99%
“…The increased expression of PPARγ directly activates or induces the gene expression profile of the majority of adipocyte phenotypes, including fatty acid synthase, glutamic acid 4, acetyl coenzyme A and shuttle enzymes (26). However, the overexpression of PPARγ in vitro inhibits the formation of fat cells and promotes the formation of osteoblasts, leading to an increase in trabecular bone (27). Studies have demonstrated that when PPARγ genes are selectively knocked out of fat cells, the function of fat cells is severely degraded, leading to progressive lipodystrophy, insulin resistance and other metabolic diseases (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, the overexpression of PPARγ in vitro inhibits the formation of fat cells and promotes the formation of osteoblasts, leading to an increase in trabecular bone (27). Studies have demonstrated that when PPARγ genes are selectively knocked out of fat cells, the function of fat cells is severely degraded, leading to progressive lipodystrophy, insulin resistance and other metabolic diseases (27,28). Fat formation is impaired in PPARγ-knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…It poses a great threat to human health and life due to its characteristics of emergent onset, further complications and a high mortality rate (18,19). The morbidity and mortality of coronary heart disease in China has been gradually rising, and the rate of increase appears to be escalating (20,21).…”
Section: Discussionmentioning
confidence: 99%